Effect of hiatus hernia on reflux patterns and mucosal integrity in patients with non‐erosive reflux disease. Issue 11 (20th May 2022) - Sawada, Akinari; Rogers, Benjamin; Visaggi, Pierfrancesco; de Bortoli, Nicola; Gyawali, C. Prakash; Sifrim, Daniel
Abstract: Background: Hiatus hernia (HH) contributes to development of gastroesophageal reflux disease, Barrett's esophagus and esophageal adenocarcinoma. This study was aimed to investigate the influence of HH on reflux patterns and distal esophageal mucosal integrity in non‐erosive reflux disease (NERD). Methods: We retrospectively analyzed PPI‐refractory NERD patients referred to three tertiary referral centers who underwent high‐resolution manometry and off‐PPI 24‐h impedance‐pH monitoring (with or without bile spectrophotometry). Patients with HH ≥2 cm (HH group, n = 42) or no HH (non‐HH group, n = 40) with similar esophageal acid exposure time (AET 6%–12%) were included. Key Results: Age, gender, BMI, esophageal motility, AET, and esophageal clearance were similar between the two groups. The HH group had higher numbers of total reflux episodes ( p = 0.015) with similar proportion of acid/non‐acid reflux compared with the non‐HH group. Mean nocturnal baseline impedance (MNBI) in the distal esophagus was significantly lower in the HH group than the non‐HH group at both 5 cm ( p = 0.002) and 3 cm ( p = 0.015) above the lower esophageal sphincter. Multivariable regression analysis showed that HH, less non‐acid reflux and lower post‐reflux swallow‐induced peristaltic wave index (PSPWI) were independently associated with lower MNBI. Among 31 patients tested with bile spectrophotometry, the HH group had significantly longer bile exposure time than the non‐HH group ( p = 0.011), and bile reflux inversely and significantly correlated with MNBI (rho = −0.75, p < 0.001). Conclusions and Inferences: Hiatus hernia, less non‐acid reflux and lower PSPWI were associated with lower MNBI. HH impairs distal esophageal mucosal integrity, the mechanism of which we speculate to be through excessive bile reflux. Abstract : In patients with similar acid burden and similar motor function, the presence of a hiatus hernia, less non‐acid reflux and lower post‐reflux swallow‐induced peristaltic wave index led to greater impairment of distal esophageal mucosal integrity compared with no hernia. HH impairs distal esophageal mucosal integrity possibly through excessive bile reflux.